Framework for engineering design systems architectures evaluation and selection: case study - Darwish, Mohamed; Shehab, Essam (Elsevier, 2017)
Engineering companies face the challenge of developing complex Engineering Design Systems. These systems involve huge financial, people, and time investments within an environment that is characterised by continuously changing technologies and processes. Systems architecture provides the strategies and modelling approaches to ensure that adequate resources are spent in developing the possible To Be states for a target system. Architecture selection and evaluation involves evaluating different architectural alternatives with respect to multiple criteria, hence an Architecture Evaluation Framework which evaluates and down selects the appropriate architectures solutions is crucial to assess how these systems will deliver value over their lifetime, and where to channel the financial and human investments to maximize benefit delivered to the business’ bottom line. In this paper, an evaluation and selection architecture framework is proposed, which targets to maximise the alignment of Engineering Design Systems with business goals based on a quality centric architecture evaluation approach. The framework utilised software Quality Attributes as well as SWOT (Strength, Weakness, Opportunity, Threat) and PEST (Political, Economic, Social, Technological) analyses to capture different viewpoints related to technical, political and business context. The framework proposed employing AHP (Analytical Hierarchy Process) to quantitatively elicit relationships between Quality Attributes trade-offs and architectural characteristics. The framework was applied to a real case study considering five Engineering Design Systems alternative architectures, where workshops with subject matter experts and stakeholders were held to reach an informative decision, that maximise architectural quality, whilst maintaining business alignment.
Keywords: Engineering design system architecutre; architecture evaluation; quality attributes; analytic hierarchy process (AHP); SWOT and PEST